Pengaruh konseling menggunakan media booklet terhadap pengetahuan dan sikap pada pasien diabetes melitus - Riza Trisda; Saipul Bakri (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: Diabetes mellitus (DM) or diabetes is a health disorder in the form of a collection of symptoms that arise in a person caused by an increase in blood sugar levels due to insulin deficiency or insulin resistance and metabolic disorders in general.Objective: To determine the effect of counseling with booklet media on knowledge, attitudes in type II diabetes mellitus patients at Iskandar Muda Kindergarten II HospitalMethods: This study is a Quasi Experiment with one group pre-test post-test design using total sampling. This research was conducted at Kindergarten II Iskandar Muda Hospital Banda Aceh in 2018. The descriptive univariate analysis includes frequency distribution and percentage, bivariate test with dependent t-testResults: It shows that there is a significant effect of counseling using booklet media in increasing knowledge (p= 0.000) and attitudes (p= 0.001) of diabetes mellitus patients in Iskandar Muda Kindergarten II hospital.Conclusion: Counseling using booklet media can increase knowledge and attitudes of type II diabetes mellitus patients.